Constructing an Islamic Socially Responsible Investment (SRI) Index; The Case of Indonesia - Wiku Suryomurti (Tazkia Islamic Finance and Business Review, 2017)
The aim of this study are: (i) to develop an index based on Islamic stock from List of Islamic Securities (DES) and integrate them with the concept of Socially Responsible Investment (SRI) and (ii) to compare the performance of the constructed index with Jakarta Islamic Index (JII) and SRI Kehati Index. We construct the index using Equally Weighted Method from extensive dataset of more than 300 Islamic securities listed in the List of Islamic Securities (DES). Our result is fairly striking as the Islamic SRI index outperform JII and SRI Kehati as well. We conclude that additional screening with ESG parameter does not impact the index performance. To our knowledge, this research is the first to introduce an Islamic SRI stock Index, particularly in Indonesia. Hence, the result could be a consideration for the Indonesia stock exchange (IDX) stakeholder to introduce this index to the market. Furthermore, the results is expected to help investors in selecting stock that meet the standards of Islamic stocks while also fulfill the ESG criteria into their investment portfolios.